Pavithra (MO 13) and Panchami (MO 14): Two gall midge resistant varieties of rice - Bai, N. Rema; Devika, R.; Leenakumary, S. (Journal of Tropical Agriculture, 2006)
Hybridization programme was started in 1985 at the Rice Research Station, Moncompu using locally accepted varieties like MO 4, MO 6, MO 7 and gall midge (GM) resistant varieties such as MO 5, Surekha, Pothana etc. using pedigree-breeding method to evolve varieties with resistance to GM Biotype 5. Up to six generation, selection was practised based on GM resistance, yield and general performance. Two cultures, KAU M59–29–2–1–2 (IET 13983) from the cross Surekha / MO 5 and KAU M61-6-1-1-2 (IET 14260) from the cross Pothana / MO 5 performed well in yield trials over the check varieties and were released as Pavithra (MO 13) and Panchami (MO 14) respectively in 1998 for use in GM endemic areas.